2020
DOI: 10.1177/0886260520966673
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Risk Factors for Non-fatal Strangulation and Post-assault Imaging

Abstract: Strangulation has long been associated with death in the context of sexual assault and intimate partner violence (IPV). Non-fatal strangulation (NFS) during sexual assault, which refers to strangulation or choking that does not result in death, is common and has been associated with IPV and with bodily injury; however, other factors associated with NFS are unknown. The current study examined demographic and sexual assault characteristics associated with NFS among women who received a sexual assault medical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The theme of failure to recognize was overwhelmingly identified across the reviewed literature, described by some authors across the continuum of care (McKee et al, 2020; Monahan et al, 2020). That is, diagnosis of NFS on ED presentation may be hindered by the presence of other significant injuries requiring intervention (Jacob et al, 2020; Kivelä et al, 2019; MacDonald et al, 2021; Stellpflug et al, 2022) and subsequent assessment for effects of NFS is not often reported, due in some way to the failure to follow up explained as the third theme in this review findings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theme of failure to recognize was overwhelmingly identified across the reviewed literature, described by some authors across the continuum of care (McKee et al, 2020; Monahan et al, 2020). That is, diagnosis of NFS on ED presentation may be hindered by the presence of other significant injuries requiring intervention (Jacob et al, 2020; Kivelä et al, 2019; MacDonald et al, 2021; Stellpflug et al, 2022) and subsequent assessment for effects of NFS is not often reported, due in some way to the failure to follow up explained as the third theme in this review findings.…”
Section: Resultsmentioning
confidence: 99%
“…Patch et al (2021) considered skin tone and time from/mechanism of injury as factors relating to bruising that may be missed during examination. McKee et al (2020) reported no apparent demographic characteristics whereas multiple other authors report age (younger more at risk) and gender (female) as risk factors (Jacob et al, 2020; Kivelä et al, 2019, Stellpflug et al, 2022). Kivelä et al (2019) went further to include risk factors of alcohol use and night‐time, whereas Patch et al (2021) included the risk factor of location, where NFS was more probably to occur in metropolitan settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, it is likely that they received this imaging due to the presence of the ED protocol, which recommended vascular imaging on all patients presenting with strangulation, regardless of the presence of neurological signs or symptoms. 20,21 In 2008, prior to the protocol initiation, only 4 of 26 patients seen for NF-IPS (15.4%) received dedicated neck imaging. By 2014, 63 of 71 patients (88.7%) received imaging-and during this time period, 2…”
Section: Discussionmentioning
confidence: 99%
“…The 2 identified cases of carotid artery dissection in our sample presented primarily with neck pain and headache, underscoring the importance of imaging to detect this potentially devastating injury. In our sample, it is likely that they received this imaging due to the presence of the ED protocol, which recommended vascular imaging on all patients presenting with strangulation, regardless of the presence of neurological signs or symptoms 20,21. In 2008, prior to the protocol initiation, only 4 of 26 patients seen for NF-IPS (15.4%) received dedicated neck imaging.…”
Section: Discussionmentioning
confidence: 99%